The relationship between technology acceptance and employee job performance at Telekom Malaysia, Kuching / Nurul Sherra Sazreen Ameran - Ameran, Nurul Sherra Sazreen (2016)
This study was conducted to investigate the relationship between the Technology Acceptance Model by Davis (1989) towards employee job performance at the Network Development Department, Telekom Malaysia, Kuching. Three factors were used for this study, including perceived usefulness, perceived ease of use and behavioral intention to use. The researcher examined whether these three factors have any impacts on staff job performance. Convenience sampling was used for this study since the staff used technology in performing their jobs. The survey instrument adapted from TAM Model was used to measure the relationship between technology acceptance factor and job performance. 160 questionnaires were distributed at the Network Development Department, Telekom Malaysia, Kuching. However, only 127 staff responded to the questionnaire. Results show that the technology acceptance factor amongst the staff at Telekom Malaysia, Kuching was positively and significantly correlated with job UT was performance. The study concludes that the technology acceptance factor has an impact on job performance as they are willing to accept the technology and are intent on using the technology. Notably, the more important the task is, the higher the intention to use the technology. Further recommendations were discussed.